Portuguese as a foreign language: initial approaches in a multicampus context - Severino, Cintia do Nascimento [UNESP]; Rocha, Nildiceia Aparecida [UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
The Portuguese language has gained prominence in the last thirty years, mainly due to the growth and development of training spaces, the rising quantity of publications in the field and the variety of studies focusing on many specific aspects of Portuguese as a Foreign Language (from now on, PLE [Portugues Lingua Estrangeira]). The modern environment of globalization, transnationalization of languages and countries, together with the proposals for the internationalization of Brazilian higher education institutions highlight the need for investment in language teaching and drive a change in the way one sees Portuguese teaching, learning and professional training. Considering the projection of the field, we aim to summarize and analyze the initial approaches in PLE in the context(s) of a multicampus institution, which, despite not offering an academic course focused on PLE, has been contributing to promote the Portuguese language and to train teachers based on teaching experiments both face-to-face or in a virtual environment and investigations, thus putting into practice the dialogue between the university pillars.
Keywords: Portuguese as a Foreign Language; Teacher education; Multicampus Context; University foundations